(untitled) (Journal of Management, 2024)
In today’s fast-changing and competitive work environment, ethical leadership is very important. It can lead to positive results for employees. This study looks at how ethical leadership affects employees’ commitment. It also examines how trust in leadership plays a role in this relationship, focusing on co-operative societies in Nepal. To achieve the objective, data were primarily collected through structured questionnaires using a convenience sampling technique from 391 employees of Nepalese cooperative societies. The data were analyzed with Process Macro 4, utilizing a 95% confidence interval and 5,000 bootstrapping samples. The results of this study indicate that ethical leadership has a significant impact on employee commitment. Additionally, leadership trust fully mediates the relationship between ethical leadership and employee commitment. This study also emphasized that leaders who demonstrate ethical behavior not only build their credibility but also cultivate a workplace culture that encourages employee loyalty and retention. It further contributes to the understanding of the ethical leadership in nurturing the employees’ commitment in their organization.